A review of biological delignification and detoxification methods for lignocellulosic bioethanol production. (September 2015) - Moreno, Antonio D.; Ibarra, David; Alvira, Pablo; Tomás-Pejó, Elia; Ballesteros, Mercedes
Abstract Future biorefineries will integrate biomass conversion processes to produce fuels, power, heat and value-added chemicals. Due to its low price and wide distribution, lignocellulosic biomass is expected to play an important role toward this goal. Regarding renewable biofuel production, bioethanol from lignocellulosic feedstocks is considered the most feasible option for fossil fuels replacement since these raw materials do not compete with food or feed crops. In the overall process, lignin, the natural barrier of the lignocellulosic biomass, represents an important limiting factor in biomass digestibility. In order to reduce the recalcitrant structure of lignocellulose, biological pretreatments have been promoted as sustainable and environmentally friendly alternatives to traditional physico-chemical technologies, which are expensive and pollute the environment. These approaches include the use of diverse white-rot fungi and/or ligninolytic enzymes, which disrupt lignin polymers and facilitate the bioconversion of the sugar fraction into ethanol. As there is still no suitable biological pretreatment technology ready to scale up in an industrial context, white-rot fungi and/or ligninolytic enzymes have also been proposed to overcome, in a separated or in situ biodetoxification step, the effect of the inhibitors produced by non-biological pretreatments. The present work reviews the latest studies regarding the application of different microorganisms or enzymes as useful and environmentally friendly delignification and detoxification technologies for lignocellulosic biofuel production. This review also points out the main challenges and possible ways to make these technologies a reality for the bioethanol industry.